Pengaruh Model Pembelajaran Make a Match Berbantuan Media Tangga Logaritma terhadap Hasil Belajar Siswa Kelas X Listrik SMK Negeri 5 Waingapu - Ariance Rambu Jola Piras; Darius Imanuel Wadu; Elsy Senides Hana Taunu (Journal on Education, 2024)
This study aims to determine the influence of the make a match model assisted by logarithmic ladder media on the learning outcomes of students in class X of Electrical Vocational School N 5 Waingapu. This study is aquantitative research with a type of experiment using a nonequivalent control group design. The population in this study is all students of class X of SMK N 5 Waingapu with the research subjects being X electricity 1 as the control class and X electricity 2 as the experimental class. The data collection techniques used in this study are pretest and posttest with a total of 10 questions. The data analysis used in this study is a descriptive analysis. The data was processed using SPSS version 21 to analyze descriptive tests, normality, homogeneity and hypothesis. The average pretest of the control class was 27.50, the posttest of the control class was 50.63 and the average of the experimental pretest was 29, 66 and 74.83. The results of this study show that there is a significant influence on student learning outcomes by using a make a match model assisted by logarithmic ladder media. Based on the hypothesis test, it shows that the significant value (2-tailed) is 0.000<0.05 so that Hₒ is rejected and Hl is accepted. It can be concluded that the media-assisted make a match model has a positive effect on the learning outcomes of class X students of SMK N 5 Waingapu Keywords: Learning Outcomes, Make A Match, Logarithmic Ladder